Position tracking of DC motor with PID controller utilising particle swarm optimisation algorithm with levy flight and doppler effect - Nur Iffah, Mohamed Azmi; Nafrizuan, Mat Yahya (Institute of Advanced Engineering and Science, 2025)
This paper presents the implementation of the PSO-LFDE (Particle Swarm Optimization with Lévy Flight Doppler Effect) algorithm for optimizing PID controller parameters in a DC motor system. Traditional optimization algorithms like PSO, WOA, GWO, and MFO often face challenges in balancing exploration and exploitation, leading to suboptimal performance. The proposed PSO-LFDE algorithm addresses these issues by incorporating Lévy Flight for enhanced exploration and the Doppler Effect for refined exploitation. The algorithm is validated using MATLAB/Simulink for position control in a DC motor system with step inputs of 10, 30, and 60 cm. Key performance metrics, including rise time, settling time, peak time, and steady-state error, were compared against other optimization methods. PSO-LFDE demonstrated superior performance, achieving a 41.63% improvement in rise time and a 70.20% reduction in peak time compared to other methods. These results highlight PSO-LFDE's effectiveness in optimizing PID controller parameters and improving the dynamic response of DC motor systems, offering a robust solution for real-world control applications.